(untitled) (Minang Chemistry Journal (MCJ), 2026)
The essential oil of Cinnamomum burmannii bark harvested in West Sumatra was extracted by steam distillation and analyzed by GC-MS. Cinnamaldehyde was identified as the major active component (74.2%). The antioxidant activity was measured using the DPPH radical scavenging assay, yielding an IC50 value of 18.5 ug/mL. These results suggest that local cinnamon essential oil has strong potential as a natural food preservative and pharmaceutical ingredient.